New approaches to countering terrorism: designing and evaluating counter radicalization and de-radicalization programs - Said, Hamed el- (New security challenges series, 2015)
Hamed El-Said investigates the emergence of new, 'soft' approaches to counter violent extremists, generally known as counter radicalization and deradicalization programmes (Counter-de-Rad). This is the first work to develop a holistic framework which will allow policy makers and practitioners to better understand conditions conducive to violent extremism, and to better design and effectively implement such programmes in the future. This book, supported and facilitated by a wealth of primary research and consideration of all stakeholders, addresses cultural and legal differences between countries while developing its holistic approach. In addition, the research focuses on and identifies conditions conducive to either the success or the failure of Counter-de-Rad programmes. Finally, it provides a new, broader approach to evaluate the performance of such programmes, one that goes beyond the current narrow models which treat recidivism rates as the main indicator of success or failure